Sex Differences in Dendritic Spine Formation in the Hippocampus and Animal Behaviors in a Mouse Model of Hyperthyroidism - Niiyama, Tetsushi; Kuroiwa, Mahomi; Yoshioka, Yusaku; Kitahara, Yosuke; Shuto, Takahide; Kakuma, Tatsuyuki; Ohta, Keisuke; Nakamura, Kei-ichiro; Nishi, Akinori; Noda, Mami (Frontiers in Cellular Neuroscience, 2020)
Among hormones, thyroid hormones are critical for the regulation of development and differentiation of neurons and glial cells in the central nervous system (CNS). We have reported the sex-dependent changes of glial morphology in the brain under the state of hyperthyroidism. Here we examined sex-dependent changes in spine structure of granule cells in the dentate gyrus of hippocampus in male and female mice with hyperthyroidism. Using FIB/SEM (focused ion beam/scanning electron microscopy), three-dimensional reconstructed structures of dendritic spines in dentate granule cells were analyzed. Dendritic spine density in granule cells was significantly increased in both male and female mice with hyperthyroidism. The decrease in spine volume was observed only in female mice. These findings suggest that hyperthyroidism induces the formation of spines with normal size in male mice, but the formation of spines with small size in female mice. To evaluate an outcome of neuronal and glial changes, behavioral tests were performed. Male mice with hyperthyroidism showed the increased locomotor activity in the open field test, while female mice showed the increased immobility time in the tail suspension test, reflecting depression-like behavior. Though it is difficult to link the complicated changes in spine and glial morphology to behavioral changes, these results may help to understand neurological and psychological symptoms observed in patients with hyperthyroidism in a sex-dependent manner.